After Saddam Prewar Planning and the Occupation of Iraq - Bensahel, Nora (RAND Corporation, 2008)
This monograph examines prewar planning efforts for the reconstruction of postwar Iraq. It then examines the role of U.S. military forces after major combat officially ended on May 1, 2003, through June 2004. Finally, it examines civilian efforts at reconstruction, focusing on the activities of the Coalition Provisional Authority and its efforts to rebuild structures of governance, security forces, economic policy, and essential services.